Gerakan Sosial dan Anarkisme: Sebuah Analisis Teoritis - Kusmana Kusmana (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
This paper explores the relationship between social movements and anarchism. Theoretically, anarchism can be categorized as a form of radical social protest. To clarify this perspective, the study separately examines the concepts and scope of social movements and anarchism while also connecting them to the broader discourses of democracy and religion. Both democracy and religion provide spaces where expressions of social movements and anarchist tendencies can emerge. By analyzing these intersections, this paper aims to provide a deeper understanding of how anarchism operates within the framework of social movements and its implications for democratic and religious contexts.